1966
DOI: 10.1111/j.1528-1157.1966.tb03804.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural Parameters and Drug Effects A Study of a Hyperkinetic Epileptic Child

Abstract: SUMMARY Traditional clinical evaluations of drug effects, with their reliance on global ratings, contrast unfavourably with the sophisticated methods employed in animal studies. In this intensive study of a hyperkinetic epileptic child an attempt was made to evaluate the differential effects of drugs on several behavioural parameters. The drugs investigated were trifluoperazine, thioridazine and sulthiame. Methods of recording and analysing the child's free‐field behaviour are described. Thioridazine was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1975
1975
1981
1981

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Greater precision in the description of the mental state is needed if the exact nature of the behavioural complication of the drugs is to be established and the possibility of characteristic effects explored. Hutt et al (1966) emphasised the importance of precise and selective descriptions of different aspects of behaviour, and advocated the abandonment of global clinical impressions which can obscure important, though selective, behavioural change. In their interesting study of the effects of different drugs on the behaviour of a hyperkinetic epileptic child, these authors reported that sulthiame had selectively beneficial effects in that it seemed to increase attention-span and to decrease destructive behaviour, whilst leaving other types of activity unchanged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Greater precision in the description of the mental state is needed if the exact nature of the behavioural complication of the drugs is to be established and the possibility of characteristic effects explored. Hutt et al (1966) emphasised the importance of precise and selective descriptions of different aspects of behaviour, and advocated the abandonment of global clinical impressions which can obscure important, though selective, behavioural change. In their interesting study of the effects of different drugs on the behaviour of a hyperkinetic epileptic child, these authors reported that sulthiame had selectively beneficial effects in that it seemed to increase attention-span and to decrease destructive behaviour, whilst leaving other types of activity unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the reported effects of sulthiame on cognitive function are similarly conflicting. Hutt et al (1966) claimed a seiectively beneficial effect of this drug on sustained attention, but a more recent report (Green et al 1974) suggests that while patients may feel more alert on sulthiame given at usual therapeutic dosage, compared with those on phenytoin they actually perform less efficiently on objective tests.…”
Section: Anti-epileptic Drugs and Learningmentioning
confidence: 99%